Internet connectivity disruption in Russia (Russia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in Russia. Data sourced from IODA.
Network Disruption Incident ID: RU-2026-0160. Severity: critical. Confidence: 65%